Zinc delays clot lysis by attenuating plasminogen activation and plasmin-mediated fibrin degradation - Henderson, Sara J.; Stafford, Alan R.; Leslie, Beverly A.; Kim, Paul Y.; Vaezzadeh, Nima; Ni, Ran; Fredenburgh, James C.; Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2015)
Zinc circulates free in plasma at a concentration of 0.1–2 μM, but its levels increase locally when it is released from activated platelets. Although zinc influences many processes in haemostasis, its effect on fibrinolysis has not been thoroughly investigated. Using a fluorescent zinc-binding probe, we demonstrated that zinc binds tissue-type plasminogen activator (tPA) and plasmin with high affinity (Kd values of 0.2 μM), and surface plasmon resonance studies revealed that zinc binds fibrin with a Kd of 12.8 μM. Zinc had no effect on the affinity of plasminogen or plasmin for fibrin, but increased the affinity of tPA by two-fold. In the presence of 5 μM zinc, the catalytic efficiency of plasminogen activation by tPA was reduced by approximately two-fold, both in the absence or presence of fibrin. Zinc attenuated plasminmediated degradation of the fibrinogen alpha-chain by 43 %, but had no effect on trypsin degradation. tPA-mediated fibrin clot lysis was prolonged 2.5-fold by zinc in a concentration-dependent fashion, and tPA-mediated plasma clot lysis was attenuated by 1.5-fold. Therefore, our data indicate that zinc modulates fibrinolysis by attenuating tPAmediated plasminogen activation and plasmin-induced fibrin degradation. These findings suggest that local release of zinc by platelets attenuates fibrinolysis.
Keywords: Zinc; fibrinolysis; fibrin; plasminogen; plasmin